A New DNA‐Intercalative Cytotoxic Allylic Xanthone from Swertia corymbosa. Issue 3 (March 2015) - Uvarani, Chokkalingam; Arumugasamy, Karuppannan; Chandraprakash, Kumarasamy; Sankaran, Mathan; Ata, Athar; Mohan, Palathurai Subramaniam
Abstract Phytochemical investigation of the CHCl3 fraction of Swertia corymbosa resulted in the isolation of a new 3‐allyl‐2, 8‐dihydroxy‐1, 6‐dimethoxy‐9H‐xanthen‐9‐one (1), along with four known xanthones, gentiacaulein (3), norswertianin (4), 1, 3, 6, 8‐tetrahydroxyxanthone (5), and 1, 3‐dihydroxyxanthone (6). Structure of compound 1 was elucidated with the aid of IR, UV, NMR, and MS data, and chemical transformation via new allyloxy xanthone derivative (2). Compounds 1–6 exhibited various levels of antioxidant and anti‐α‐glucosidase activities. Absorption and fluorescence spectroscopic studies on 1–6 indicated that these compounds could interact with calf thymus DNA (CT‐DNA) through intercalation and with bovine serum albumin (BSA) in a static quenching process. Compound 1 was found to be significantly cytotoxic against human cancer cell lines HeLa, HCT116, and AGS, and weakly active against normal NIH 3T3 cell line.